The KEAP1-NRF2 System in Healthy Aging and Longevity - Daisuke Matsumaru; Hozumi Motohashi (MDPI AG, 2021)
Aging is inevitable, but the inherently and genetically programmed aging process is markedly influenced by environmental factors. All organisms are constantly exposed to various stresses, either exogenous or endogenous, throughout their lives, and the quality and quantity of the stresses generate diverse impacts on the organismal aging process. In the current oxygenic atmosphere on earth, oxidative stress caused by reactive oxygen species is one of the most common and critical environmental factors for life. The Kelch-like ECH-associated protein 1-NFE2-related factor 2 (KEAP1-NRF2) system is a critical defense mechanism of cells and organisms in response to redox perturbations. In the presence of oxidative and electrophilic insults, the thiol moieties of cysteine in KEAP1 are modified, and consequently NRF2 activates its target genes for detoxification and cytoprotection. A number of studies have clarified the contributions of the KEAP1-NRF2 system to the prevention and attenuation of physiological aging and aging-related diseases. Accumulating knowledge to control stress-induced damage may provide a clue for extending healthspan and treating aging-related diseases. In this review, we focus on the relationships between oxidative stress and aging-related alterations in the sensory, glandular, muscular, and central nervous systems and the roles of the KEAP1-NRF2 system in aging processes.